MATHEMATICAL MODELING OF DRYING OF TOMATO SLICES USING INFRARED RADIATION - Doymaz, Ibrahim (WILEY, 2014)
The effect of different infrared power levels on the drying kinetics and rehydration capacity of tomato slices was investigated. The tomatoes were cut into eighths and dried at different infrared power levels. It was observed that the power levels affected the drying time and rehydration capacity. Drying time was reduced from 450 to 240 min as the infrared power level increased from 125 to 188 W. The experimental data obtained from drying study were fit with nine mathematical models to evaluate the drying kinetics of tomato slices. The fit quality of the proposed models was evaluated using the determination of coefficient, mean relative percent error, reduced chi-square and root mean square error. Among the nine drying models, the model of Midilli et al. showed the best fit of drying kinetics of tomato slices. Effective moisture diffusivity varied from 2.66 to 5.17 X 10(-9) m(2)/s and was significantly influenced by infrared power.
Keywords: EFFECTIVE MOISTURE DIFFUSIVITY; KINETICS; QUALITY; DEHYDRATION; APPLES; GRAPE; FRESH; Food Science & Technology